Functional relationship of room temperature and setting time of alginate impression material - Dyah Irnawati; Siti Sunarintyas (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Indonesia is a tropical country with temperature variation. A lot of dental clinics do not use air conditioner. The room temperature influences water temperature for mixing alginate impression materials. Purpose: The aim of this study was to investigate the functional relationship of room temperature and initial setting time of alginate impression materials. Methods: The New Kromopan® alginate (normal and fast sets) were used. The initial setting time were tested at 23 (control), 24, 25, 26, 27, 28, 29, 30 and 31 degrees Celcius room temperatures (n = 5). The initial setting time was tested based on ANSI/ADA Specification no. 18 (ISO 1563). The alginate powder was mixed with distilled water (23/50 ratio), put in the metal ring mould, and the initial setting time was measured by test rod. Data were statistically analyzed by linear regression (α = 0.05). result: The initial setting times were 149.60 ± 0.55 (control) and 96.40 ± 0.89 (31° C) seconds for normal set, and 122.00 ± 1.00 (control) and 69.60 ± 0.55 (31° C) seconds for fast set. The coefficient of determination of room temperature to initial setting time of alginate were R2 = 0.74 (normal set) and R2 = 0.88 (fast set). The regression equation for normal set was Y = 257.6 – 5.5 X (p < 0.01) and fast set was Y = 237.7 – 5.6 X (p < 0.01). Conclusions: The room temperature gave high contribution and became a strength predictor for initial setting time of alginates. The share contribution to the setting time was 0.74% for normal set and 0.88% for fast set alginates.